Azithromycin Improved FD Symptoms - Nichols, Emma Hitt (MD Conference Express, 2014)
Characterized by neutrophilic inflammation of the scalp, folliculitis decalvans (FD) has an unknown etiology and results in painful, recurrent purulent follicular exudation. Azithromycin treatment in patients with FD resulted in a significant decrease in the number of papules and pustules on the scalp and improved the global subjective score, as discussed in this article.